Beyond potency: A proposed lexicon for sensory differentiation of Cannabis sativa L. aroma - Isaacson, Solomon E.; Wilson-Poe, Adrianne R.; Ye, Tingting; Qian, Yanping L.; Shellhammer, Thomas H. (PLOS ONE, 2025)
Aroma is a critical factor in consumer-perceived quality of Cannabis sativa L., yet standardized tools for describing the aromatic diversity of uncombusted Cannabis inflorescence are lacking. This study generated and evaluated a descriptive aroma lexicon for intact Cannabis inflorescence consisting of 25 terms with defined reference standards. A human panel evaluated 91 samples using a Check-All-That-Apply method. Multivariate analyses demonstrated the lexicon’s ability to differentiate samples based on orthonasal aroma. Type I and III Cannabis exhibited overlapping sensory profiles, though type I (high THC, low CBD) was more frequently described as skunky, musty, and animalic, whereas type III (low THC, high CBD) had higher frequencies of citrus, fruity, and candy-like aromas. Terpene profiling revealed clear chemical clusters, but terpene profiles alone poorly predicted sensory character. Terpinolene was the only compound consistently associated with sensory descriptors, specifically citrus and chemical. In type III samples, 43 volatile sulfur compounds were detected via gas chromatography with a pulsed flame photometric detector, including dimethyl sulfide, methional, and dimethyl trisulfide while others were tentatively identified or novel. However, neither terpene nor volatile sulfur compound profiles strongly predicted sensory perception. These results emphasize the limitations of chemical composition as a proxy for aroma quality. This work establishes a foundation for future research linking aroma, chemistry, and consumer preferences, and supports the development of quality metrics beyond delta-9-tetrahydrocannabinol potency.